Soil Fertility Assessment and Mapping of Agricultural Research Station, Jaubari, Illam, Nepal - Khadka, Dinesh; Lamichhane, Sushil; Shrestha, Keshav; Joshi, Sushila; Karna, Manoj; Pant, Buddhi B.; Yadav, Surendra (International Journal of Environment, 2017)
Soil fertility evaluation is a prerequisite factor for sustainable planning of a particular region. Considering this, a study was conducted to determine the soil fertility status of the Agricultural Research Station, Jaubari, Illam, Nepal. In total, 78 soil samples were collected using soil sampling auger randomly from a depth of 0-20 cm. The texture, pH, OM, N, P2O5, K2O, Ca, Mg, S, B, Fe, Zn, Cu and Mn status of the samples were analyzed in the laboratory of Soil Science Division, Khumaltar by following standard analytical methods. The soil fertility maps of the observed parameters were prepared through Arc-GIS 10.1 software. The observed data revealed that soil was brown (10YR 4/3), dark grayish brown (10YR 4/2), dark yellowish brown (10YR 4/4) and yellowish brown (10YR 5/6) in colour, and the structure was granular. Similarly, the sand, silt and clay content were 53.84±1.06%, 34.34±0.83% and 11.82±0.47%, respectively and were indicated as sandy loam and loam in texture. The soil was very acidic (pH 3.85±0.04), and very low in available boron (0.26±0.06mg/kg) and available sulphur (0.59±0.15mg/kg). The available calcium (188.7±31.30mg/kg), available magnesium (50.98±5.0mg/kg) and available manganese (5.16±0.90mg/kg) were low. Likewise, available potassium (110.91±7.30mg/kg), available zinc (1.19±0.31mg/kg) and available copper (0.95±0.05mg/kg) content were medium. Similarly, organic matter (7.88±0.32%), total nitrogen (0.27±0.01%) and available phosphorus (36.53±5.66mg/kg) were high, and available iron (39.5±2.17 mg/kg) was very high.  International Journal of EnvironmentVolume-6, Issue-3, Jun-Aug 2017, page: 46-70